2013
DOI: 10.1063/1.4829702
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of nanocrystalline KNbO3

Abstract: Newly synthesized undoped and iron-doped nanoscale powders of KNbO3 are investigated using magnetic resonance and static magnetization methods in order to determine how the crystal size and doping affect the structure of magnetic defects and material properties. Although the bulk crystals of KNbO3 are nonmagnetic, the undoped KNbO3 powder with average particle size of 80 nm exhibits magnetic properties. The ferromagnetic resonance signal and the magnetization curve registered on the powder are thoroughly analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 16 publications
3
18
0
Order By: Relevance
“…Classical examples are unexpected experimental results of Yadlovker and Berger [16,17,18], which reveal the enhancement of polar properties of cylindrical nanoparticles of Rochelle salt. Frey and Payne [19], Zhao et al [20], Drobnich et al [21], Erdem et al [22] and Golovina et al [23,24,25] demonstrate the possibility to control the phase transitions (including new polar phases appearance) for BaTiO3, S2P2S6, PbTiO3 and KTa1-хNbхO3 nanopowders and nanoceramics by finite size effects.…”
Section: Introductionmentioning
confidence: 99%
“…Classical examples are unexpected experimental results of Yadlovker and Berger [16,17,18], which reveal the enhancement of polar properties of cylindrical nanoparticles of Rochelle salt. Frey and Payne [19], Zhao et al [20], Drobnich et al [21], Erdem et al [22] and Golovina et al [23,24,25] demonstrate the possibility to control the phase transitions (including new polar phases appearance) for BaTiO3, S2P2S6, PbTiO3 and KTa1-хNbхO3 nanopowders and nanoceramics by finite size effects.…”
Section: Introductionmentioning
confidence: 99%
“…Frey and Payne [108], Zhao et al [109], and Erdem et al [110] demonstrated a possibility to control the temperature of a ferroelectric phase transition, as well as the magnitude and position of a dielectric permittivity maximum, for BaTiO 3 and PbTiO 3 nanopowders and nanoceramics. The research of KTa 1− Nb O 3 nanopowders [111] and ceramic nanograins [112][113][114] revealed the emergence of new polar phases and a shift of the phase transition temperature with respect to that in bulk crystals. The size effects were detected in SrBi 2 Ta 2 O 9 nanoparticles by Yu et al [115] and Ke et al [116], by using Raman spectroscopy.…”
Section: Multiferroic Nanoparticles the State Of Artmentioning
confidence: 99%
“…It was established experimentally that extrinsic and intrinsic defects play a crucial role in the impurities [9,13,49]. It is known that the concentration of defects inside the crystal is inhomogeneous and strongly increases when going from the bulk to the surface of the particle [49].…”
Section: Ii1 Model Background For Ktao 3 -Knbo 3 Systemmentioning
confidence: 99%